Synergistic galvanic-pitting corrosion of copper electrical pads treated with electroless nickel-phosphorus/immersion gold surface finish. (July 2017) - Salahinejad, E.; Eslami Farsani, R.; Tayebi, L.
Abstract: This paper reports a study on the corrosion damage of a copper pad coated with electroless nickel-phosphorus/immersion gold in a sulfur-containing atmosphere. For this purpose, the surface and cross section of the pad showing localized corrosion products were analyzed by optical microscopy, scanning electron microscopy/energy-dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy. According to the results, slightly nickel and predominantly copper suffered from corrosion attacks, accompanied by the formation of mainly sulfide with a small fraction of sulfate. Considering the characterized configurations of the pad and corrosion products, a sequential mechanism was established to interpret the galvanic-pitting corrosion attack of both species. In this regard, the nanoporous immersion gold surface acted as the cathode in the bimetallic degradation of nickel, whereas the environmental attack of copper was accelerated because of its electrical contact with cathodic nickel and gold via the formation of a trimetallic galvanic microcell. Highlights: The board failed due to the galvanic-pitting corrosion of a Cu/Ni-P/Au multilayer. The corrosion products were Cu and Ni sulfide and sulfate, based on XPS. The porosity of the top layer of Au played a critical role.